2019
DOI: 10.1016/j.jdent.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pulpotomy for mature carious teeth with symptoms of irreversible pulpitis: A systematic review

Abstract: was reduced to 93.97% clinical and 88.39% radiographic success at 36 months follow-up. Results from the only comparative clinical trial showed pulpotomy to have comparable success to root canal treatment at 12, 24 and 60 month follow-up. Conclusions The evidence suggests high success for pulpotomy for teeth with signs and symptoms of irreversible pulpitis, however, results are based on heterogeneous studies with high risk of bias. Well-designed, adequately powered randomised controlled trials are required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 32 publications
(49 reference statements)
7
135
0
1
Order By: Relevance
“…Different types of study designs -prospective, retrospective and randomized controlled trials -were included in this systematic review. The success rate of coronal pulpotomy was found 97.4% clinically and radiographically 95.4% at 12-month follow-up [29].…”
Section: Reviewmentioning
confidence: 79%
“…Different types of study designs -prospective, retrospective and randomized controlled trials -were included in this systematic review. The success rate of coronal pulpotomy was found 97.4% clinically and radiographically 95.4% at 12-month follow-up [29].…”
Section: Reviewmentioning
confidence: 79%
“…In past years, convergent results from the literature suggested that permanent vital teeth with pulpitis may be treated using full pulpotomy. Several studies have shown similar success rates for full pulpotomy compared to root canal treatment (RCT) [ 39 ]. It might be expected that full pulpotomy will become the endodontic treatment of choice for affected teeth with a vital pulp, instead of RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pulpitis is prone to necrosis because the pulp is in a closed pulp chamber, lack of effective collateral circulation [1]. In clinic, pulp drying therapy, plasticization therapy and root canal therapy are effective methods to treat pulpitis, but both root canal therapy and other pulp therapy are at the cost of sacrificing part or whole of the pulps [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The pulp is mainly connected to the outside of the tooth through the narrow apical foramen and the lack of effective collateral circulation and the absence of concessional environment [1]. It is not easy to establish suitable drainage when the pulp is inflamed.…”
Section: Introductionmentioning
confidence: 99%